HDL-C as a novel predictor of immune reconstitution in people living with HIV: insights from a baseline-to-dynamic change cohort study in China, 2005–2022 - Li, Xiaorui; Sun, Liqin; He, Yun; Zhao, Fang; Luo, Yinsong; Liu, Chenye; Hu, Yiyao; Jiang, Yuxin; Lu, Hongzhou; Liu, Jiaye (Frontiers in Immunology, 2025)
BackgroundHigh-density lipoprotein cholesterol (HDL-C) is a well-established marker of lipid metabolism and increasingly recognized as an indicator of inflammatory status. This study investigates HDL-C’s role as a predictor of immune reconstitution in people living with HIV (PLWH).MethodsWe performed a prospective cohort study of 15,434 PLWH initiating antiretroviral therapy at the Third People’s Hospital of Shenzhen, China, between 2005 and 2022. Baseline quartile grouping and Group-Based Trajectory Modeling (GBTM) explored the relationship between HDL-C and immune reconstitution. Restricted cubic spline plots identified nonlinear association.ResultsOver a median follow-up of 17.9 months, 9,609 PLWH achieved the CD4+ T-cell count of 500 cells/μL or higher. Multivariate-adjusted Cox proportional hazards regression model showed that hazard ratios (HR) [95% confidence intervals (CI)] for CD4+ T-cell recovery in Q2, Q3, and Q4 versus Q1 of the HDL-C were 0.94 (95% CI: 0.88-0.99), 0.92 (95% CI: 0.87-0.98), and 0.85 (95% CI: 0.80-0.91), respectively. GBTM identified two HDL-C trajectories: Low-floating and High-floating. Relative to Low-floating, High-floating demonstrated a reduced likelihood of CD4+ T-cell recovery (HR=0.86, 95% CI: 0.82-0.90, p < 0.001). A nonlinear association was observed between HDL-C and the outcome (p for nonlinear association = 0.037, p for overall < 0.001), with a threshold at 1.13 mmol/L. Negative correlations between HDL-C and CD4+ T-cell recovery were observed both below the threshold (HR=0.72, 95% CI: 0.57-0.92) and above the threshold (HR=0.78, 95% CI: 0.69-0.87) (both p < 0.05).ConclusionsOur study highlights HDL-C’s role in immune recovery, suggesting its potential in guiding prevention and treatment strategies for PLWH.